1995
DOI: 10.1016/0896-6273(95)90267-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of the low affinity neurotrophin receptor (p75) in retrograde axonal transport of the neurotrophins

Abstract: The receptor mechanisms mediating the retrograde axonal transport of the neurotrophins have been investigated in adult rats. We show that transport of the TrkB ligands NT-4 and BDNF to peripheral neurons is dependent on the low affinity neurotrophin receptor (LNR). Pharmacological manipulation of LNR in vivo using either an anti-LNR antibody or a soluble recombinant LNR extracellular domain completely blocked retrograde transport of NT-4 and BDNF to sensory neurons, while having minimal effects on the transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
3
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(135 citation statements)
references
References 61 publications
9
121
3
2
Order By: Relevance
“…In contrast, NT4/5 can also bind efficiently to the NT3 high-affinity sites (Fig. 3), in line with previous studies using neurotrophin mutants (Rydén et al, 1995) and retrograde transport in vivo (Curtis et al, 1995), indicating a selective interaction of NT4/5 with p75 N TR .…”
Section: Neuronal P75 Ntr Forms High-affinity Selective Nt3 Receptorssupporting
confidence: 72%
“…In contrast, NT4/5 can also bind efficiently to the NT3 high-affinity sites (Fig. 3), in line with previous studies using neurotrophin mutants (Rydén et al, 1995) and retrograde transport in vivo (Curtis et al, 1995), indicating a selective interaction of NT4/5 with p75 N TR .…”
Section: Neuronal P75 Ntr Forms High-affinity Selective Nt3 Receptorssupporting
confidence: 72%
“…Excess BDNF vesicles transported to the neurite terminal that are not captured by stimulation would then be expected to return to the cell body for degradation, or perhaps even reuse, to maintain homeostasis. While retrograde transport of BDNF from the postsynaptic terminal has been reported (Bhattacharyya et al, 2002;Curtis et al, 1995;DiStefano et al, 1992;Reynolds et al, 2000;Yano and Chao, 2004), it is unlikely that the BDNF-GFP vesicles we observed moving in the retrograde direction in hippocampal neurons represent vesicles that was released and endocytosed, since we were studying unstimulated neurons. Besides, the BDNF-GFP signal in such putative vesicles, if generated, would be far too weak to be detected.…”
Section: Discussionmentioning
confidence: 89%
“…p75 NTR is internalized and retrogradely transported, but it does not appear to be down-regulated from the cell surface in response to NGF (M.G., D. Hall, A. Schroepfel, and W.M., unpublished observations) (63)(64)(65). Moreover, p75 NTR does not appear to play a significant role in the retrograde transport of NGF, but does transport other neurotrophins (66,67). These findings suggest that p75 NTR does not play a role in survival-promoting retrograde signaling by NGF.…”
Section: Resultsmentioning
confidence: 99%